Difficult conversations: exploring the practitioner role in applying theatre and drama techniques for adult training in UK educational settings - Hargreaves, Gary (2025)
This thesis explores Applied Theatre (AT) with a focus on Forum Theatre (FT) and their processes in my work and the work of another experienced educational theatre practitioner in the UK. As researcher, I examine and reflect on a range of Applied Theatre practices, focusing on three events in UK educational settings. The key theme of these events, common in much AT and FT work is difficult conversations. I adopted an reflective research methodology, as it aligns with Jackson’s genealogical critical theories in the development of Applied Theatre (Jackson, 2006). To this end I use autoethnography as a central instrument in reflecting on the research, drawing on autobiographical contextual life story vignettes that are used reflexively and retrospectively. My positionality is embedded fundamentally in this autoethnographic approach. The research explores the nature of reflection and importance of reflexivity in the development of my AT practice. The study aimed to discover how AT practice and practitioners who use applied drama and theatre techniques as a means of change and transformation have evolved. In the progression and processes of AT practice, there has been an increasing demand for clear ethical guidelines or a framework. Some suggestions of what might be useful in an ethical framework, or guidelines, are suggested as outcomes of this research. My research draws primarily on the AT practices that have their origins and roots derived from Augusto Boal’s Forum Theatre and are heavily influenced by the education and critical theorist, Paulo Freire (Freire, 1970) and his dialogical pedagogical practice. This study provides a deeper understanding of FT practitioner work. With an ever-growing body of FT practice, this research supports the development and efficacy of my own practice, with the potential to inform current AT practice and future training, and offers advice for potential ethical guidance or frameworks.